Nerve root compression caused by intraspinal gas accumulation. A case report - A. Daškevičiūtė; R. Bunevičiūtė; J. Sejonienė (Neurologijos seminarai)
Vacuum disc phenomenon is a condition frequently seen with degenerative disc disease and is characterized by the collection of gas in the disc space. In rare cases, gas accumulation can spread into the intraspinal canal. When it occurs, clinical symptoms may be observed. We present a case report of S1 nerve root compression caused by intraspinal gas accumulation. Diagnosis of the disease was complicated by the fact that magnetic resonance imaging had not revealed intraspinal gas accumulation. The diagnosis was confirmed only by computed tomography findings.